O racismo como tema transversal na formação acadêmica de psicólogas(os) em Santa Maria - RS - Santos, Ticiane Lúcia dos (2022)
Since the colonial era, the Brazilian population has been facing consequences of the racist ideology that maintains the racial hierarchy from which the White population benefits materially and symbolically, whereas the Black population fights against social inequality for centuries. Studying racism within the structure of Brazilian society is fundamental to understanding how the process of subjectivation occurs through racial markers, causing psychosocial effects that can be observed in the psychology practice. This study was drawn aiming to comprehend whether the content about racism takes part in the academic training and education of psychologists. This study was characterized as a qualitative, descriptive and exploratory research and had the participation of fourteen psychologists in the city of Santa Maria - RS. The researcher used as instruments for collecting the information, a field diary written, an online questionnaire and a semi-structured interview and the hermeneuticdialectical analysis was used to analyze the information. The results are organized and presented in the following three articles: 1- The first article discusses the comprehension of psychologists towards racism; 2- The second presents the study about racism during psychology academic training; 3- The third article contains a debate about decoloniality as a theoretical and social intervention program that may assist the process of (re)construction of psychology curriculum. The study concludes that the interviewed psychologists understand the importance of the markers of race and racism in the process of subjectivation of Brazilians, and even though the topic was often absent in their undergraduate curriculums, these professionals have been seeking training in racial issues. Therefore, this study defends changes in the structure of the academic psychology curriculum through guidelines and similar resources that shall consider mandatory contents to be taught such as racism, in order to obtain more contextualized and socially relevant training. We understand that decoloniality is a critical perspective capable of referencing this search for a diversified curriculum that may integrate social realities.